Blessed Peter 'Monoculus,' Abbot of Igny, then of Clairvaux, France - Merton, Thomas (Cistercian studies quarterly, 2002)
Focuses on the life of Blessed Peter Monoculus, Abbot of Igny and Clairvaux in France. Academic background of the abbot; Physical ailments suffered by Blessed Peter; Reputation of Blessed Peter in Italy.